Opened 8 years ago

Closed 8 years ago

# primdecSY fails to decompose example?

Reported by: Owned by: kroeker@… decker minor 4-1-0 and higher dontKnow 4-0-1 decompose bug minpoly

### Description

the failing example:

```LIB("primdec.lib");
ring rng = (7,vv),(x,y,z,u),(dp(4),C);
minpoly = (vv^2+vv+3);
ideal I = (2*vv+3)*y^2*z+(2*vv+1)*y^2+(vv-2),(-3*vv-1)*x*z^2+(vv)*x^2+(-3*vv-1)*z^2,(3*vv)*x^3+(-vv);
def L1 = primdecSY (I); // fails?
def L2 = primdecSY ( std(I) );
size(L1); // =1
size(L2); // =2
```

output

```> L1;
[1]:
[1]:
_[1]=x^2+(2*vv-2)*z^2-2*x+2
_[2]=z^3+2*x^2+(-3*vv-1)*y^2+(2*vv+3)*x*z-3*z^2+(-2*vv+2)*x+(3*vv-2)*z+(2*vv+3)
_[3]=x*z^2+(-2*vv+3)*x^2+z^2
_[4]=y^2*z+(-3*vv-1)*y^2-3
_[5]=x*y^2-3*z^3+x^2+y^2+(vv+1)*x*z+2*z^2+(vv-3)*x+(-2*vv-2)*z+(-2*vv-3)
_[6]=y^4-2*x^2+(2*vv-2)*y^2+(-2*vv-3)*x*z+2*z^2+(2*vv+3)*x+(3*vv+2)*z+(2*vv+2)
[2]:
_[1]=x^2+(2*vv-2)*z^2-2*x+2
_[2]=z^3+2*x^2+(-3*vv-1)*y^2+(2*vv+3)*x*z-3*z^2+(-2*vv+2)*x+(3*vv-2)*z+(2*vv+3)
_[3]=x*z^2+(-2*vv+3)*x^2+z^2
_[4]=y^2*z+(-3*vv-1)*y^2-3
_[5]=x*y^2+(-2*vv-2)*y^2+3*x*z+(2*vv+3)*x-z+(-3*vv-1)
_[6]=y^4-2*x^2+(2*vv-2)*y^2+(-2*vv-3)*x*z+2*z^2+(2*vv+3)*x+(3*vv+2)*z+(2*vv+2)
> L2;
[1]:
[1]:
_[1]=x*z+(-3*vv+2)*y*z+(2*vv+1)*z^2+(2*vv-1)*x+(2*vv-3)*y-2*z+(2*vv+1)
_[2]=y^2+(vv)*x*z+y*z+(-3*vv+3)*z^2+(-vv+2)*x+(3*vv-2)*y+(vv+3)*z+(2*vv)
_[3]=x*y-2*y^2+2*x*z+3*y*z+(-2*vv+1)*x+(-vv)*y+(-3*vv-1)*z+(-3*vv+2)
_[4]=x^2+3*y^2+2*x*z+y*z-z^2+(3*vv-1)*x-y+(2*vv-2)*z+(-vv+1)
_[5]=z^3+2*y^2+x*z-y*z+(3*vv-2)*x+(-3*vv)*y+(2*vv-2)*z+(-3*vv)
_[6]=y*z^2-2*y^2+2*x*z-2*y*z-2*z^2-2*x+(3*vv-1)*y+(-3*vv+2)*z+(-3*vv+2)
[2]:
_[1]=x*z+(-3*vv+2)*y*z+(2*vv+1)*z^2+(2*vv-1)*x+(2*vv-3)*y-2*z+(2*vv+1)
_[2]=y^2+3*x*z-2*y*z+(-3*vv-2)*z^2+(vv-2)*x+2*y+(3*vv-3)*z+(2*vv+2)
_[3]=x*y-2*y^2+2*x*z+3*y*z+(-2*vv+1)*x+(-vv)*y+(-3*vv-1)*z+(-3*vv+2)
_[4]=x^2+3*y^2+2*x*z+y*z-z^2+(3*vv-1)*x-y+(2*vv-2)*z+(-vv+1)
_[5]=z^3+(-2*vv+1)*x*z-3*y*z+(-vv+1)*z^2+(-2*vv+1)*x+(-2*vv-3)*y-z
_[6]=y*z^2+(-vv)*y^2+(vv-1)*x*z-2*y*z+(-vv+1)*z^2+(3*vv+3)*x+(-2*vv-1)*y+(vv+2)*z
[2]:
[1]:
_[1]=x*z+(3*vv-2)*y*z+(2*vv+1)*z^2+(2*vv-1)*x+(-2*vv+3)*y-2*z+(2*vv+1)
_[2]=y^2+(vv)*x*z-y*z+(-3*vv+3)*z^2+(-vv+2)*x+(-3*vv+2)*y+(vv+3)*z+(2*vv)
_[3]=x*y+2*y^2-2*x*z+3*y*z+(2*vv-1)*x+(-vv)*y+(3*vv+1)*z+(3*vv-2)
_[4]=x^2+3*y^2+2*x*z-y*z-z^2+(3*vv-1)*x+y+(2*vv-2)*z+(-vv+1)
_[5]=z^3+2*y^2+x*z+y*z+(3*vv-2)*x+(3*vv)*y+(2*vv-2)*z+(-3*vv)
_[6]=y*z^2+2*y^2-2*x*z-2*y*z+2*z^2+2*x+(3*vv-1)*y+(3*vv-2)*z+(3*vv-2)
[2]:
_[1]=x*z+(3*vv-2)*y*z+(2*vv+1)*z^2+(2*vv-1)*x+(-2*vv+3)*y-2*z+(2*vv+1)
_[2]=y^2+3*x*z+2*y*z+(-3*vv-2)*z^2+(vv-2)*x-2*y+(3*vv-3)*z+(2*vv+2)
_[3]=x*y+2*y^2-2*x*z+3*y*z+(2*vv-1)*x+(-vv)*y+(3*vv+1)*z+(3*vv-2)
_[4]=x^2+3*y^2+2*x*z-y*z-z^2+(3*vv-1)*x+y+(2*vv-2)*z+(-vv+1)
_[5]=z^3+(-2*vv+1)*x*z+3*y*z+(-vv+1)*z^2+(-2*vv+1)*x+(2*vv+3)*y-z
_[6]=y*z^2+(vv)*y^2+(-vv+1)*x*z-2*y*z+(vv-1)*z^2+(-3*vv-3)*x+(-2*vv-1)*y+(-vv-2)*z

```

### comment:1 Changed 8 years ago by barakat

Owner: changed from somebody to decker

### comment:2 Changed 8 years ago by hannes

Resolution: → fixed new → closed
Note: See TracTickets for help on using tickets.